James Bond in barracuda run - Otfinoski, Steven (New York, U.S.A. : Ballantine Books, 1985)
You are James Bond, vacationing on the island paradise of Tahiti. After a frighteningly close brush with killer sharks, you learn that your latest assignment involves a barracuda! But this barracuda is no fish. Instead it is a top-secre weapon - a supersonic submarine that is vitually unstoppable. Your mission? To prevent the Barracuda from being hijacked by Dr. Hans Glaub, an infamous ex-Nazi who is reportedly conducting experiments involving brain implants and genetic engineering.
Keywords: ENGLISH LITERATURE; SHORT STORIES